Surkhandarya Agricultural Industry During the Second World War - B. S. Safarov (Peerian Journals Publishing, 2022)
This article covers the cultivation and processing of agricultural products during World War II. It also discusses the political processes that flourished during World War II. It also examines the challenges of growing cotton and the barriers and processes involved in the delivery of raw cotton.
Keywords: The Presidium of the Supreme Soviet of the USSR; industry; fortune - teller Kojeneva,; Merzlikina